Toll-like receptor 4 gene polymorphisms and susceptibility to juvenile idiopathic arthritis. Issue 5 (21st October 2004) - Lamb, R; Zeggini, E; Thomson, W; Donn, R
Abstract : Objectives: To determine if polymorphisms within the Toll-like receptor 4 (TLR4) gene are associated and linked with juvenile idiopathic arthritis (JIA). To investigate any possible gene-gene (epistatic) interaction between TLR4 and macrophage migration inhibitory factor (MIF) gene polymorphisms. Methods: 313 simplex families (each containing one affected JIA proband) were genotyped. Two known functionally important single nucleotide polymorphisms (SNPs) within the TLR4 gene (Asp299Gly and Thr399Ile) were typed by SNaPshot ddNTP primer extension and capillary electrophoresis. Single point and multipoint transmission disequilibrium tests (TDT) were carried out through the extended TDT and TDT phase packages for the two TLR4 SNPs. Epistatic interaction between TLR4 haplotypes and the previously JIA associated MIF CATT7 -MIF-173*C promoter haplotype was investigated by χ 2 test and unconditional logistic regression in Stata version 7. Results: No distortion from random inheritance was observed by single point analysis for TLR4 Asp299Gly (p = 0.89) or TLR4 Thr399Ile (p = 0.40). Similarly, no distortion in transmission was seen when the TLR4 haplotypes were studied (p = 0.54). Additionally, no evidence for gene-gene interaction between TLR4 polymorphisms and the previously associated MIF gene polymorphisms was found (p = 0.40). Conclusions: No linkage or association was seen for Asp299Gly or Thr399Ile SNPs of TLR4 with JIA susceptibility. No evidence of an epistatic interaction between these TLR4 polymorphisms and MIF polymorphisms was found.